Predicting Progression of Intracranial Arteriopathies in Childhood Stroke With Vessel Wall Imaging. Issue 8 (August 2017) - Stence, Nicholas V.; Pabst, Lisa L.; Hollatz, Amanda L.; Mirsky, David M.; Herson, Paco S.; Poisson, Sharon; Traystman, Richard J.; Bernard, Timothy J.
Abstract : Background and Purpose—: Childhood arterial ischemic stroke is frequently associated with an intracranial arteriopathy that often progresses in the first 3 to 6 months post stroke. We hypothesized that children with enhancing arteriopathies on vessel wall imaging (VWI) would have a higher risk of arteriopathy progression than those without enhancement. Methods—: Our institutional radiographic database was searched for cases of childhood stroke with VWI. Inclusion criteria consisted of age ranging from 1 month through 20 years, diagnosis of arterial ischemic stroke, available VWI, and follow-up magnetic resonance angiogram. Imaging was reviewed to systematically describe VWI findings, categorize arteriopathies, steroid therapy, and identify progressive arteriopathies using CACADE definitions. Results—: Sixteen cases of childhood stroke at Children's Hospital Colorado between January 1, 2010 and July 1, 2016 were reviewed. Strong vessel wall enhancement at presentation was associated with progressive arteriopathy in 83% of cases (10/12), when compared with 0% (0/4) without strong enhancement ( P =0.008). Conclusions—: Our case series demonstrates the potential benefit of VWI in children with stroke because it may identify patients who will have progressive arterial disease. Abstract : Supplemental Digital Content is available in the text.